A guide to mental health for families and carers of people with intellectual disabilities - Holt, Geraldine, 1951-; Gratsa, Anastasia, 1945-; Bouras, Nick. (London ; Philadelphia, Pa. : Jessica Kingsley, 2004)
A practical and comprehensive introduction for carers to mental health problems, this accessible guide outlines a range of signs and symptoms of mental health problems that can affect people with intellectual disabilities. The guide explains why mental health problems develop, and advises on what can be done to help people with intellectual disabilities and carers themselves. With chapters on specific disabilities such as autism and epilepsy, the authors cover topics such as: treatment and interventions for mental health problems; getting the best services and understanding policy around menta.
Cover; Guide to Mental Health for Families and Carers of People with Intellectual Disabilities; Contents; ACKNOWLEDGEMENTS; FINDING YOUR WAY AROUND THIS GUIDE; What is this Guide for?; 1 General Information Regarding Mental Health Problems; 2 Mental Health Problems; 3 Services for People with Intellectual Disabilities and Mental Health Problems; 4 Therapeutic Interventions; 5 Challenging Behaviour; 6 Law, Policy and Ethical Issues; 7 Autism; 8 Epilepsy; 9 Carers' Needs and Support; APPENDIX: INFORMATION FROM THE MENTAL HEALTH ACT (1983); FURTHER READING AND RESOURCES; GLOSSARY.
Includes bibliographical references (pages 224-226) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: People with mental disabilities -- Mental health; People with mental disabilities -- Family relationships; People with mental disabilities -- Care; Mental Disorders -- complications; Intellectual Disability -- complications; Caregivers; Family Relations; Persons with Intellectual Disabilities -- rehabilitation; Personnes ayant une déficience intellectuelle -- Relations familiales; Personnes ayant une déficience intellectuelle -- Soins; Care Of The Mentally Ill; PSYCHOLOGY -- Mental Health; PSYCHOLOGY -- Mental Illness; MEDICAL -- Mental Health; People with mental disabilities -- Care; People with mental disabilities -- Family relationships; People with mental disabilities -- Mental health